Familial multiple sclerosis: MRI findings in clinically affected and unaffected siblings. - Tienari, P J (1992)
Subclinical demyelinating lesions may occur in the brains of asymptomatic individuals, and the first-degree relatives of multiple sclerosis (MS) patients are at particular risk. Clinical and MRI examinations were performed in nine sibships from families with two or more cases of MS. These included 14 patients with clinically definite MS, three patients with clinically probable MS, and 27 asymptomatic siblings. Systematic criteria were applied to MRI interpretations to increase their specificity for MS. Thirteen (76%) of the 17 patients with MS showed lesions suggesting MS. Lesions were also found in six (38%) of the 16 asymptomatic siblings under age 50 and in eight (73%) of the 11 over age 50. Judged by stringent criteria, the lesions of only three (11%) of the 27 asymptomatic siblings were considered to be due to demyelination. The results demonstrate the occurrence of subclinical demyelination in asymptomatic siblings of MS patients and stress the importance of clinical follow up and MRI studies of the first-degree relatives when classifying them as healthy in family studies.